2019
DOI: 10.1016/j.envres.2018.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Household fuel use and pulmonary tuberculosis in western Nepal: A case-control study

Abstract: BACKGROUND: Whether cooking with solid fuels, as occurs widely in developing countries, including Nepal, is a risk factor for pulmonary tuberculosis (PTB) is uncertain. Epidemiologic studies have produced variable results. This case-control study sought to resolve this issue with a large sample size and a population-based control group. METHODS: PTB cases (N = 581), aged 18 to 70 were recruited from diagnostic centers in Kaski and neighboring districts of Nepal. Population-based controls (N = 1,226) were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…In indoor air, exposures to fine particles are from the combustion of household fuels and poor ventilation in the kitchen 10 , 18 . Both kitchen ventilation and household combustions associate with TB, especially in women 14 , 15 , 18 , 53 . In this context, data were compiled under the category kitchen, which had three independent variables, namely, (i) kitchen location (KLO) (partitioned inside the house (PIH) or non-partitioned inside the house (NPIH)), (ii) cooking fuel uses (CFU) (LPG or solid fuels) and (iii) ventilation in the kitchen (VEN) (at least one window of size 2ft by 2ft or no window).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In indoor air, exposures to fine particles are from the combustion of household fuels and poor ventilation in the kitchen 10 , 18 . Both kitchen ventilation and household combustions associate with TB, especially in women 14 , 15 , 18 , 53 . In this context, data were compiled under the category kitchen, which had three independent variables, namely, (i) kitchen location (KLO) (partitioned inside the house (PIH) or non-partitioned inside the house (NPIH)), (ii) cooking fuel uses (CFU) (LPG or solid fuels) and (iii) ventilation in the kitchen (VEN) (at least one window of size 2ft by 2ft or no window).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies 15 21 have shown that exposure to fine particulate matter (PM 2.5 ; particles of size less than or equal to 2.5 microns) from burning biomass, smoking, kerosene fuel, vehicular pollution, etc. trigger the risk of TB infection and full-blown disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial basis for the selection of study participants was households of control participants in a pulmonary tuberculosis (TB) case-control study carried out in and around Kaski District, Nepal [2,4], with the objective of obtaining 300 participants from households, with a balanced distribution of the three main fuels used in this area in primary stoves for cooking: LPG, wood, and biogas. Participants in the present study were required to be women, who do most of the cooking in Nepal, aged 40-70 years.…”
Section: Study Setting and Participantsmentioning
confidence: 99%